2007
DOI: 10.1111/j.1471-6712.2007.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of arthritis on daily life with the patient perspective in focus

Abstract: The results of this study support the view that more psychosocial support is required to encourage the recently diagnosed RA patient in the new situation of having a chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 27 publications
4
82
2
2
Order By: Relevance
“…These studies found that illness uncertainty was a salient experience for all of these pain conditions. Uncertainty was associated with diffi culties in adaptation to these conditions and led to more anger and depression [50]. A study of patients with low back pain found that those who experienced uncertainty were driven to reduce the distress of uncertainty by utilizing a multitude of coping strategies, changing attitudes about pain, and continuing to search for medical certainty despite feeling stigmatized by their health care providers [49].…”
Section: Other Chronic Illnessesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies found that illness uncertainty was a salient experience for all of these pain conditions. Uncertainty was associated with diffi culties in adaptation to these conditions and led to more anger and depression [50]. A study of patients with low back pain found that those who experienced uncertainty were driven to reduce the distress of uncertainty by utilizing a multitude of coping strategies, changing attitudes about pain, and continuing to search for medical certainty despite feeling stigmatized by their health care providers [49].…”
Section: Other Chronic Illnessesmentioning
confidence: 99%
“…Qualitative studies A number of qualitative studies also have examined the concept of illness uncertainty in the context of chronic pain conditions, including low back pain, RA, and unexplained chest pain [46][47][48][49][50][51] (Table 1). These studies found that illness uncertainty was a salient experience for all of these pain conditions.…”
Section: Other Chronic Illnessesmentioning
confidence: 99%
“…[14][15][16][17] Kleinman 18 differentiated between the notions of disease as described from a medical perspective and illness as a daily life experience. The daily life experience of chronic illness might be explored through several themes, such as loss, threat to identity, 19 and physical changes to the body.…”
Section: Older and Chronically Ill Personsmentioning
confidence: 99%
“…Strategies to ensure optimal RA care include allowing the patient to play a more active role in their disease management (Berry et al, 2003;Lutze and Archenholtz, 2007), and an overall trend towards enhancing the role of the patient in the rehabilitation of chronic diseases have been described (Iversen and Petersson, 2006;Kjeken et al, 2006;Lempp et al, 2006). The healthcare system needs to adapt more fully to the patient perspective (Arvidsson et al, 2006;Kjeken et al, 2006).…”
Section: Introductionmentioning
confidence: 98%